Gender difference on the relationship between hyperuricemia and nonalcoholic fatty liver disease among Chinese: An observational study. Issue 39 (September 2017) - Yu, Xiao-Long; Shu, Long; Shen, Xiao-Ming; Zhang, Xiao-Yan; Zheng, Pei-Fen
Abstract : Abstract: Limited evidence is available regarding the association between serum uric acid (SUA) and nonalcoholic fatty liver disease (NAFLD), especially in gender difference. Therefore, this study aimed to evaluate gender difference on the association between SUA, hyperuricemia, and NAFLD in the Chinese population. A cross-sectional study was carried out in a group of 1006 Chinese adults aged between 45 and 59 years old, in the city of Hangzhou, Zhejiang Province who were attending their annual health examination in the period between July 2015 and March 2017. Face-to-face interviews were conducted using a written questionnaire. Multivariate logistic regression analysis was performed to examine the associations between SUA, hyperuricemia, and NAFLD with adjustment of potential confounding variables. Wald tests were used to for heterogeneity between males and females. Body mass index (BMI), waist circumference (WC), waist–hip ratio (WHR), fasting plasma glucose (FPG), systolic blood pressure (SBP), diastolic blood pressure (DBP), triglycerides (TG), SUA, alanine aminotransferase (ALT), asparagine aminotransferase (AST), and the prevalence of hypertension, hyperuricemia, and NAFLD were significantly higher in male than in female ( P < .05). Females had the significantly higher levels of total cholesterol and high-density lipoprotein–cholesterol (HDL-C). Simple correlation analysis showed that SUA was positively associated with BMI, WC, WHR, TG, ALT, AST and inversely associated with age and HDL-C. After adjusting for confounders, hyperuricemia was associated with an increased risk of NAFLD in both genders, with odds ratio (95%confidence interval) of 2.645 (1.213–5.768), 1.962 (1.051–3.661), respectively. There was a significant association in NAFLD found in males, compared with females (Wald = 118.589, df = 1, P < .0001). Our findings indicated that the association of SUA with NAFLD was much more closely related in males than in females. Males with hyperuricemia had the higher risk of NAFLD. Further longitudinal studies are needed to confirm these findings.